Blood pressure, serum cholesterol concentration and their related factors in urban and rural elderly of Ho Chi Minh city [Viet Nam] - Tran T.M.H. (Tokushima Univ. (Japan). School of Medicine); Komatsu, T; Nguyen, T.K.H; Nguyen, V.C; Yoshimura, Y; Takahashi, K; Wariishi, M; Sakai, T; Yamamoto, S (Journal of Nutritional Science and Vitaminology, 2001)
In Vietnam, information about blood pressure, serum lipids and their factors is limited. To obtain some of this information, a cross sectional nutrition survey was carried out in an urban and rural area of Ho Chi Minh City with 217 participants aged 60-69 y (148 females and 69 males). Anthropometry and blood pressure were measured. For three consecutive weekdays, 24 h dietary recalls were performed. Single 24 h urine was collected for sodium and potassium analysis. A fasting blood sample was taken and biochemical parameters were measured. Results indicate a high percentage of hypertension in urban (female: 35.5%, male: 43.8%) and rural areas (female: 22.2%, male: 35.1%). Blood pressure was correlated with body mass index (BMI) and 24 h urinary sodium-to-potassium (Na/K) ratio. A high prevalence of serum total cholesterol (TC) above 220 mg/dL (female: 55.3%, male: 31.3%) and overweight (female: 34.2%, male: 25.0%) were observed in urban residents. By contrast, 5.6% and 24.3% of rural females and males respectively had TC below 150 mg/dL and both genders had the same prevalence of underweight (32.4%). TC was positively correlated with boty weight, BMI, dietary protein and dietary lipids. Overweight might be a major risk factor for hypertension in our urban elderly. A high Na/K intake ratio might be a risk factor for hypertension in both areas. The high prevalence of elevated TC in the urban area might to be related to the high lipid intake, and the high prevalence of low TC in the rural area might to be related to the low lipid intake.